Enunciation process and enunciatary construction in the women magazine "Cosmopolitan" - Merlino, Aldo (Círculo de Lingüística Aplicada a la Comunicación, 2013)
In this paper we analyze how a graphic media suggest to their readers a certain enunciatary model. Such suggestion is put at stake through certain enunciation strategies. Then, reconstructing those strategies we define the enunciatary model suggested by the magazine and the way it can work as an “identification mirror” for the readers.